Evaluation of a mycotoxin adsorbent in swine diets containing barley naturally contaminated with Fusarium mycotoxins - Kong, Changsu; Sol Park, Chan; Gyun Kim, Beob (Revista Colombiana de Ciencias Pecuarias, 2016)
contamination of barley with Fusarium mycotoxins causes significant economic losses for pork producers, and alleviation with mycotoxin sequestering agents has proven inconsistent. Objective: to evaluate a yeast cell wall product in preventing adverse effects of Fusarium mycotoxins on growth performance, blood characteristic, and nutrient digestibility in gilts fed diets containing barley naturally contaminated with Fusarium mycotoxins. Methods: positive and negative controls of corn-soybean meal diets containing 20% control and contaminated barley with Fusarium mycotoxins, respectively, were prepared. Two additional diets were prepared by adding 0.2 or 0.4% of a yeast cell wall product to the negative control diet. The experimental diets were fed to pigs with 61.7 Kg initial body weight for 2 weeks. Results: pigs fed the negative control diet gained less than those fed the positive control diet (p < 0.05) from d 0 to 7 and during the overall period, but nutrient digestibility and blood characteristics were not affected by feeding the contaminated diet. Most measurements were not affected by supplementing the yeast cell wall to the negative control diet. Conclusion: addition of the yeast cell wall product to negative control diets failed to ameliorate the adverse effects of dietary Fusarium mycotoxin on growth performance.